Mecz bokserski o mistrzostwo kl. B Mewa-Lechia. (Gdańsk : [s.n.], 1948)
Afisz inf. o meczu bokserskim 09.05.1948 r. w gdańskim Domu Marynarza.
Keywords: Boks -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne